2018
DOI: 10.1145/3161184
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Suitability of Service Animals Using Instrumented Dog Toys

Abstract: Working dogs1 are significantly beneficial to society; however, a substantial number of dogs are released from time consuming and expensive training programs because of unsuitability in behavior. Early prediction of successful service dog placement could save time, resources, and funding. Our research focus is to explore whether aspects of canine temperament can be detected from interactions with sensors, and to develop classifiers that correlate sensor data to predict the success (or failure) of assistance do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Lormier and colleagues [42] found that canine fear and aggression are behaviors responsible for dismissal from assistance training programs. Currently, the costs of raising and training an assistance dog are as high as US$50,000 [18]. Genetic screening of dogs for insertions at WBSCR17 may assist in identifying social predispositions of dogs early in development, which could increase successful training and placement of assistance dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lormier and colleagues [42] found that canine fear and aggression are behaviors responsible for dismissal from assistance training programs. Currently, the costs of raising and training an assistance dog are as high as US$50,000 [18]. Genetic screening of dogs for insertions at WBSCR17 may assist in identifying social predispositions of dogs early in development, which could increase successful training and placement of assistance dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Assistance dog training programs explicitly survey behaviors that are imperative to their program’s success, and include robustness to environmental stressors, social behaviors, trainability, attention, and problem-solving [6]. However, these programs often document up to 60% failure rates [18], with behavioral problems reported as one of the primary causes for dismissal. For instance, 60% of dogs that are withdrawn from the Guide Dogs for the Blind program for behavioral reasons that include high activity level, incompatibility with cats or other dogs, and assertiveness toward leadership [19].…”
Section: Introductionmentioning
confidence: 99%
“…Another method of predicting service dog suitability is to use objective data provided by sensors. Byrne et al [7] used instrumented dog toys with sensors to develop a logistic model tree to classify outcomes in a service dog organization (Canine Companions for Independence) and were able to achieve accuracy of 87.5%. They calculated that this could save $70,000 by identifying dogs that will likely fail the program.…”
Section: Related Workmentioning
confidence: 99%
“…Byrne et al [54] have recently proposed a technological approach to predict the suitability of dogs for assistive dog training programs. The authors have explored whether aspects of canine temperament can be detected from dogs' interactions with sensors embedded in two instrumented dog toys: a silicone ball and a silicone tug sensor.…”
Section: Tangible and Physical Objectsmentioning
confidence: 99%